FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN DI TOKO MM 46 WAY JEPARA LAMPUNG TIMUR - Yanti, Dian Apri; Efendi, Nur; Djausal, Gita Paramita (Jurnal Kompetitif Bisnis, 2023)
The retail business is a business that is growing rapidly and shifting traditional markets. This opportunity provides an opportunity for those who want to open a retail business. This study aims to determine the factors that influence purchasing decisions at the MM 46 Way Jepara store. This type of research is exploratory research using a quantitative approach. The sampling technique uses an accidental sampling technique and uses a non-probability sample method with a total sample of 100 MM Shop consumers. The data analysis used was multiple linear regression analysis with the SPSS 26.0 application tool. The results show that partially the price and product variety variables have a significant influence on purchasing decisions, while the location variable has no significant effect on purchasing decisions. While the simultaneous results of location, price, and product variety together have a significant influence on consumer purchasing decisions at the MM 46 Way Jepara Store, East Lampung.